Identification of hospitalized patients with community-acquired infection in whom treatment guidelines do not apply: a validated model. (24th December 2019) - Cardoso, Teresa; Rodrigues, Pedro Pereira; Nunes, Cristina; Almeida, Mónica; Cancela, Joana; Rosa, Fernando; Rocha-Pereira, Nuno; Ferreira, Inês; Seabra-Pereira, Filipa; Vaz, Prudência; Carneiro, Liliana; Andrade, Carina; et al.
Abstract: Objectives: To develop and validate a clinical model to identify patients admitted to hospital with community-acquired infection (CAI) caused by pathogens resistant to antimicrobials recommended in current CAI treatment guidelines. Methods: International prospective cohort study of consecutive patients admitted with bacterial infection. Logistic regression was used to associate risk factors with infection by a resistant organism. The final model was validated in an independent cohort. Results: There were 527 patients in the derivation and 89 in the validation cohort. Independent risk factors identified were: atherosclerosis with functional impairment (Karnofsky index <70) [adjusted OR (aOR) (95% CI) = 2.19 (1.41–3.40)]; previous invasive procedures [adjusted OR (95% CI) = 1.98 (1.28–3.05)]; previous colonization with an MDR organism (MDRO) [aOR (95% CI) = 2.67 (1.48–4.81)]; and previous antimicrobial therapy [aOR (95% CI) = 2.81 (1.81–4.38)]. The area under the receiver operating characteristics (AU-ROC) curve (95% CI) for the final model was 0.75 (0.70–0.79). For a predicted probability ≥22% the sensitivity of the model was 82%, with a negative predictive value of 85%. In the validation cohort the sensitivity of the model was 96%. Using this model, unnecessary broad-spectrum therapy would be recommended in 30% of cases whereas undertreatment would occur in only 6% of cases. Conclusions: For patients hospitalized with CAI and none of the following risk factors: atherosclerosis with functional impairment; previous invasive procedures; antimicrobial therapy; or MDRO colonization, CAI guidelines can safely be applied. Whereas, for those with some of these risk factors, particularly if more than one, alternative antimicrobial regimens should be considered.